Espectroscopia Raman aplicada ao mineral zircão : estudo da influência do annealing e ataque químico em traços de fissão fósseis e induzidos - Arinos, Natali Félix (2020)
The Fission Track Method is a mineral dating method based on the density and length of fission tracks contained in the crystalline structures of minerals. Zircon (ZrSiO4) due to its physical and chemical characteristics, has wide application, requiring a better understanding of its behavior. The fission tracks (amorphous region created due to the passage of fission fragments) can be generated spontaneously (thousands of years in nature) or induced in the laboratory, by bombarding the sample with thermal neutrons. In this research, we used Raman Spectroscopy to compare the response of minerals that were damaged by spontaneous fission (old crystal structure) and induced fission (new crystal structure) in the face of chemical attack and annealing processes. The zircon samples containing induced fission tracks showed a higher number of waves when subjected to annealing processes. However, when compared with samples containing tracks of fossil fission, a decrease in the wave number is noted, indicating a lower order in its crystalline structure. Samples with induced fission tracks should have greater crystallinity since they were subjected to a annealing to remove damage contained in the grain’s crystalline structure. In addition, samples with track fossil fission submitted to annealing greater than 550 ºC showed an increase in the wave number at half height, indicating a decrease in grain crystallinity. The previous annealing process generated amorphous phases in the irradiated grains, a process demonstrated by the variation in the wave number of these samples towards smaller numbers.